Recklinghausen’s disease. Hyperparathyroidism - Forrisi, Carlos; Bortagaray, Carlos A; Belzarena, Luis A; Santo, Alfredo S; Fernández, Adolfo (Cirugía del Uruguay, 2020)
Presented at session 12th November 1958